Big Sisters - Jakiela, Pamela; Ozier, Owen; Fernald, Lia; Knauer, Heather (World Bank, Washington, DC, 2020)
This paper models household investments in young children when parents and older siblings share caregiving responsibilities and when investments by older siblings contribute to young children's human capital accumulation. To test the predictions of the model, the paper estimates the impact of having one older sister (as opposed to one older brother) on early childhood development in a sample of rural Kenyan households with otherwise similar family structures. Older sibling gender is not related to household structure, subsequent birth spacing, or other observable characteristics, so the presence of an older girl (as opposed to an older boy) is treated as plausibly exogenous. Having an older sister rather than an older brother improves younger siblings' vocabulary and fine motor skills by more than 0.1 standard deviations. Viewed through the lens of the model, the empirical pattern shown here suggests that: (i) older siblings' investments in young children contribute to their human capital accumulation, and (ii) households perceive lower returns to investing in older girls than in older boys.